Low concentrations of neutrophil extracellular traps induce proliferation in human keratinocytes via NF-kB activation. Issue 1 (October 2017) - Tonello, Stelvio; Rizzi, Manuela; Migliario, Mario; Rocchetti, Vincenzo; Renò, Filippo
Highlights: NETs display a negative as well as positive role in various diseases. NETs modulate human keratinocytes behaviour through NF-kB activation. NETs could have a physiological role in normal wound healing process. Abstract: Introduction: Granulocytes play a pivotal role in innate immune response, as pathogen invasion activates neutrophils, a subclass of granulocytes, inducing the production of neutrophil extracellular traps (NETs). In this study, it has been evaluated how NETs could affect human keratinocytes (HaCaT cells) behaviour. Materials and methods: HaCaT cells were treated with increasing NETs concentrations (0.01–200 ng/ml) and the effect on cell proliferation was evaluated by MTT assay. Inhibition studies were performed by pre-treating cells with dexamethasone, chloropromazine or amiloride. NF-kB pathway activation was evaluated by western blot. Results: HaCaT cells stimulation with increasing concentrations of NETs (0.01–50 ng/ml) for 48 h resulted in a modulation of cell proliferation with a maximum increase corresponding to 0.5–1 ng/ml stimulation. NETs low concentrations not only increased cell proliferation, but were also able to induce a faster wound closure in an in vitro scratch assay. NETs scaffold, composed by histone proteins and DNA, is recognized by Toll Like Receptor 9 (TLR 9) that, in turn, activates the NF-kB pathway. In fact, NETs induced proliferation was inhibited by chloropromazine (1 nM), that blocks chlatrin vesicles formation, and by amiloride (50 nM) that inhibits macropinocytosis. Moreover, dexamethasone, an inhibitor of NF-kB, was able to abolish the NETs effect. Discussion: This study thus demonstrates that low NETs concentrations undergo internalization finally resulting in a quick NF-kB pathway activation and HaCaT cells proliferation increase, suggesting a close relationship between first immune response and wound healing onset.